2021
DOI: 10.1038/s41598-021-95933-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel inhibitor of liver cancer cell invasion and proliferation through regulation of Akt and Twist1

Abstract: When primary cancer faces limited oxygen and nutrient supply, it undergoes an epithelial–mesenchymal transition, which increases cancer cell motility and invasiveness. The migratory and invasive cancer cells often exert aggressive cancer development or even cancer metastasis. In this study, we investigated a novel compound, 3-acetyl-5,8-dichloro-2-((2,4-dichlorophenyl)amino)quinolin-4(1H)-one (ADQ), that showed significant suppression of wound healing and cellular invasion. This compound also inhibited anchora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…ADQ was shown to reduce Twist1 and increase E‐cadherin protein levels but did not affect transcription of the Twist1 gene 163 . Interestingly, ADQ also inhibits the Akt pathway, but this effect appears to be distinct from its anti‐Twist1 activity 163 in contrast with findings by Way et al which showed that emodin suppressed Twist1‐induced Akt activation 156 …”
Section: Twist1mentioning
confidence: 93%
See 4 more Smart Citations
“…ADQ was shown to reduce Twist1 and increase E‐cadherin protein levels but did not affect transcription of the Twist1 gene 163 . Interestingly, ADQ also inhibits the Akt pathway, but this effect appears to be distinct from its anti‐Twist1 activity 163 in contrast with findings by Way et al which showed that emodin suppressed Twist1‐induced Akt activation 156 …”
Section: Twist1mentioning
confidence: 93%
“…and increase E-cadherin protein levels but did not affect transcription of the Twist1 gene. 163 Interestingly, ADQ also inhibits the Akt pathway, but this effect appears to be distinct from its anti-Twist1 activity 163 in contrast with findings by Way et al which showed that emodin suppressed Twist1-induced Akt activation. 156 While most identified Twist1 inhibitors reduce Twist1 protein level but not mRNA levels, the monoterpene thymoquinone, found in abundance in the seeds of the black caraway plant (Nigella sativa), 164 was revealed to deplete CD44 + breast cancer stem cells and reduce Twist1 gene expression by nearly 80% in MCF-7 breast cancer cells.…”
Section: Targeting Twist1 With Small Moleculesmentioning
confidence: 94%
See 3 more Smart Citations